E-GOVERNMENT UTILIZATION AND THE POLITICAL LOGIC OF NETWORK GOVERNANCE IN INDONESIA’S LOCAL ADMINISTRATION - Anggraini, Dewi; Sudirman, Faturachman Alputra; Atnan, Nur; Husain, Muhammad Najib (Universitas Padjadjaran, 2025)
This article investigates the utilization of E-Government applications within the framework of network governance in Indonesia’s local administration. Drawing on both qualitative and quantitative methods, this study captures public perceptions of electronic information-based government services and explores the political and institutional dynamics underlying their implementation. Data were collected through questionnaires, document analysis, interviews, and focus group discussions (FGDs) with purposively selected informants, including leaders and staff from local government institutions. The findings demonstrate that e-government platforms enhance service efficiency, transparency, and public satisfaction. Moreover, these applications promote openness in financial management and intra-organizational communication, contributing to greater trust and comfort among citizens. Framed within the theory of network governance, the study reveals how digital service delivery is not merely a technical process but a political one—shaped by inter-institutional collaboration, administrative adaptability, and the evolving role of the state in a digitally mediated environment. These insights affirm the growing necessity of integrating digital infrastructure with political and organizational readiness to achieve effective and sustainable governance in the digital age.